Risk Factors for Lung Cancer in Non-smoking Women, North Sumatera, Indonesia - Indra Buana; Noni Novisari Soeroso; Setia Putra Tarigan; Elisna Syahruddin (Talenta Publisher, 2025)
Background: Basic Health Research Data in 2018 reported that lung cancer in women in Indonesia ranked third after breast cancer. A person's risk of developing lung cancer can be evaluated by looking at age, genetic predisposition, tobacco use, and exposure to toxic agents. Objective: To obtain data on several risk factors associated with the incidence of lung cancer in non-smoking women at Adam Malik General Hospital and Santa Elisabeth General Hospital. Methods: This case-control matching study involved 224 research subjects through medical record data collection from January 2019 to December 2020. All subjects were confirmed by questionnaires related to risk factors: age, exposure to cigarette smoke (passive smokers), genetics, exposure to firewood, and air pollution. Data were analyzed by logistic regression test. Results: The average age in the case group was 57.86 years; in the control group, 47.4 years. Five risk factors influenced lung cancer incidence: age (p = 0.008), passive smokers (p = 0.043), genetic factors (p < 0.001), exposure to firewood (p = 0.007), and air pollution (p = 0.041). Conclusion: Risk factors that significantly influence lung cancer incidence in non-smoking women are age over 40 years, genetic factors, passive smoking, and exposure to firewood.